Organizational improvisation and organizational agility as drivers of open innovation - Al-Olimat, Safa Suliman; Alshaer, Sawsan A.; Alshaar, Amaal Mohammad Khalil; Alkshali, Shaker Jaralla (International Journal of Innovative Research and Scientific Studies, 2026)
Studies examining innovation in general and open innovation in particular indicate that innovation often requires improvisation by business management. At the same time, organizations’ adoption of innovation requires a certain degree of agility that enables them to respond to changes in the innovation process. This study aims to investigate the impact of organizational improvisation on open innovation, and whether organizational agility plays a mediating role in this impact in Jordanian extractive and mining industries companies. The study relied on a descriptive quantitative approach. Data was collected using a closed-ended questionnaire based on a five-point scale, which was distributed electronically to 313 managers selected using a stratified random sampling mechanism at the top and middle levels of management. A total of 286 valid questionnaires were retrieved for statistical analysis. Data was analyzed and study hypotheses were tested using SmartPLS 4. The results of the study indicated that there is a significant impact of organizational improvisation on open innovation, and organizational improvisation has a significant impact on organizational agility, and organizational agility has a significant impact on open innovation, and that organizational agility plays a partial mediating role in the relationship between organizational improvisation and open innovation. For organizations to develop innovative products, they must rely on internal innovations, which are generated through the efforts of their employees, in addition to leveraging the innovations of others. All of this requires organizations to give their managers sufficient space to make creative decisions, take calculated risks, and rely on spontaneity and experience. All of this is supported by agile management to ensure rapid response to changes during the innovation process. The study recommended organization for enhancing the elements of organizational improvisation, including attracting talent, providing opportunities for everyone to work in teams, and empowering these teams. Organizations must foster an enabling environment that encourages employees to seek opportunities by motivating individuals to innovate and exploring diverse innovative tools and methods to cultivate a culture of open innovation. For achieving agility organization must structure the organization in a way that considers both stability and dynamism.